2011
DOI: 10.5539/jedp.v1n1p146
|View full text |Cite
|
Sign up to set email alerts
|

Second-order Mental State Attribution in Children with Intellectual Disability: Cognitive Functioning and Some Educational Planning Challenges

Abstract: Second-order mental state attribution in two groups of children with non-specific intellectual disability and Down syndrome was investigated. The children were compared to overall mental age-matched group of typically developing children. The aim of the present study was to determine the specificity of the theory of mind deficit to different groups of children with intellectual disability. The results clearly showed that children with Down syndrome performed more poorly than the children with non-specific inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
4
6
0
Order By: Relevance
“…Children with ID had significantly inferior ToM competences than children with TD. Our results reflect those obtained by other studies (Abbeduto et al, 2004;Alevriadou & Giaouri, 2011;Giaouri, Alevriadou, & Tsakiridou, 2010;Thirion-Marissiaux & Nader-Grosbois, 2008b, 2008c.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Children with ID had significantly inferior ToM competences than children with TD. Our results reflect those obtained by other studies (Abbeduto et al, 2004;Alevriadou & Giaouri, 2011;Giaouri, Alevriadou, & Tsakiridou, 2010;Thirion-Marissiaux & Nader-Grosbois, 2008b, 2008c.…”
Section: Discussionsupporting
confidence: 92%
“…From a meta-analysis exploring the development of ToM in children, it was found that desires are understood before the step of understanding false beliefs (Wellman & Liu, 2004), a step that corresponds to the moment children become aware that other people's thoughts may differ from their own (Astington & Edward, 2010). Various studies have shown that, compared to children with TD, children with ID are somewhat delayed with respect to ToM related to understanding the causes and consequences of emotions, and have difficulty understanding beliefs (Abbeduto et al, 2004;Alevriadou & Giaouri, 2011;Giaouri, Alevriadou, & Tsakiridou, 2010;Thirion-Marissiaux & Nader-Grosbois, 2008b, 2008c). Baurain and Nader-Grosbois (2013) established a positive correlation between ToM and emotional regulation, and social adjustment.…”
Section: Theory Of Mindmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, research has shown that ToM among people with intellectual disabilities is not absent but merely delayed (Baurain & Nader-Grosbois, 2013). This delay is caused by problems in such areas as reduced communication skills and language acquisition (Resches & Pérez-Pereira, 2007), relatively high egocentrism (Thirion-Marissiaux & Nader-Grosbois, 2008c) and the impaired development of executive functions (Cornish et al, 2005) among children with intellectual disabilities compared to typically developing children (Alevriadou & Giaouri, 2011;Thirion-Marissiaux & Nader-Grosbois, 2008a, 2008b.…”
Section: Theory Of Mind Development Among Children With Intellectuamentioning
confidence: 99%
“…Secondly, the present authors were able to observe that ToM among school-aged children with mild intellectual disabilities develops significantly and this effect is rather strong (slope = 0.60, SE = 0.06; p < 0.001). Other research studies show how and how much children with intellectual disabilities differ from their peers with other disorders and from peers without disabilities in the case of ToM(Alevriadou & Giaouri, 2011;Baurain & Nader-Grosbois, 2013;Yirmiya et al, 1996;1998), but do not show whether ToM develops in time. Thus, our result, showing visible positive changes in socio-cognitive functioning in this group, seems important and could…”
mentioning
confidence: 94%